Gender Invariance of the Gambling Behavior Scale for Adolescents (GBS-A): An Analysis of Differential Item Functioning Using Item Response Theory - Donati, Maria Anna; Chiesi, Francesca; Izzo, Viola A.; Primi, Caterina (Frontiers in Psychology, 2017)
As there is a lack of evidence attesting the equivalent item functioning across genders for the most employed instruments used to measure pathological gambling in adolescence, the present study was aimed to test the gender invariance of the Gambling Behavior Scale for Adolescents (GBS-A), a new measurement tool to assess the severity of Gambling Disorder (GD) in adolescents. The equivalence of the items across genders was assessed by analyzing Differential Item Functioning within an Item Response Theory framework. The GBS-A was administered to 1723 adolescents, and the graded response model was employed. The results attested the measurement equivalence of the GBS-A when administered to male and female adolescent gamblers. Overall, findings provided evidence that the GBS-A is an effective measurement tool of the severity of GD in male and female adolescents and that the scale was unbiased and able to relieve truly gender differences. As such, the GBS-A can be profitably used in educational interventions and clinical treatments with young people.